Indonesia Analisis SIG Berdasarkan Data Geologi dan Geospasial sebagai Inovasi Mitigasi Tanah Longsor Studi Kasus Daerah Wukirsari Imogiri: Indonesia - Hafid Rizki Nur Rohman; Farizki Budi Pangestu; Aan Munandar (Jurnal Studi Inovasi, 2022)
Indonesia is a country with a high level of landslides, one of which is the Imogiri area of ??Bantul, especially Wukirsari Village. The Wukirsari area is an area that has a morphology in the form of rolling hills and is traversed by the Opak Fault, causing the area to be prone to landslides that can cause physical losses and casualties. This condition is the background for conducting this research by observing the geological conditions, land use, rainfall, and slope in the area to carry out an innovation analysis based on a geographic information system that produces a map of the level of vulnerability to landslides in the research area. The research area has a hilly morphology that is steep to steep with constituent rocks in the form of pyroclastic rocks incorporated in the Semilir Formation and volcanic breccias incorporated in the Nglanggeran Formation and composed of latosol soil textured from clay to sand. The research area also found geological structures that developed in the form of faults and also rainfall conditions of more than 2000mm/year with land use dominated by forests and plantations. This research produces a map of low, medium, and high landslide susceptibility zones which are dominated by moderate vulnerability. The results of the study can be used as the main information in efforts to mitigate landslides in the Wukirsari, Imogiri, Bantul areas.